Pelajar Papua dalam Kuasa Simbolik (Studi Terhadap Reproduksi Kelas Sosial di SMK Negeri 1 Obaa, Mappi, Papua) - Mua, Marianus Muharli (Jurnal Sosiologi Agama, 2017)
In this study shown that at SMK Negeri 1 Obaa located in Mappi, Papua turns performing two roles namely the role of production and reproduction of social classes. Social class reproduction occurs because internelization of habitus, culture, taste and mindset of classes conducted by both the school and the students themselves. Through regulations and discipline imposed by the school has established habitus students and interaction among students as a means of hegemony students to follow habitus, tastes, culture and mindset of the social upper class. This school serves as a structure that perpetuates violence and symbolic power of the lower classes. At the school became the battle arena and fight to maintain the existing capital ie economic capital, social capital, cultural capital and symbolic capital. Through mastery of existing capital, schools producing and reproducing social classes. For the lower social classes it is a production that will raise the social status while the upper class it is a top-class reproduction and dominance. However, the impact of symbolic domination that occurred in this school makes the lower class who do not have the capital to be eliminated. In addition, the school culture is the culture of the dominant class so delivers lower classes in Mappi are still dominated by hunting and gathering are not able to adapt to school culture into pressure and not as important in their lives. Keywords: Schools, Gaps, Reproduction, Social Class, Strategy, Attorney Symbolic